2019
DOI: 10.1016/j.adolescence.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Narrative coherence, psychopathology, and wellbeing: Concurrent and longitudinal findings in a mid‐adolescent sample

Abstract: Introduction: Research with adults and older adolescents has found that people exhibiting higher narrative coherence in life stories also report higher psychological wellbeing; however, this link has not been investigated longitudinally. The current study investigated concurrent and longitudinal relationships in mid-adolescence between narrative coherence (causal and thematic coherence) of turning point narratives and psychopathology (depressive symptoms and rumination) and psychological wellbeing (life satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 44 publications
7
39
2
1
Order By: Relevance
“…We created 16 narratives (in Dutch) based on themes that are very common in this sample and representative for self-reported events with high emotional impact. We wrote the stories, based on our extensive experience collecting and coding hundreds of narratives in similar samples of our own studies (in prep), and investigating event types in similar work [25,26,36] We used 4 positive (graduation, falling in love, birthday party, travelling) and 4 negative themes (suicide of a friend, divorce of parents, passing away of a grandparent, end of a relationship), about which we wrote a coherent and an incoherent story each. Subsequently, two colleagues specialized in the field independently and blind for condition coded these 16 narratives for coherence using the Narrative Coherence Coding Scheme (NCCS; [24]).…”
Section: Materials and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We created 16 narratives (in Dutch) based on themes that are very common in this sample and representative for self-reported events with high emotional impact. We wrote the stories, based on our extensive experience collecting and coding hundreds of narratives in similar samples of our own studies (in prep), and investigating event types in similar work [25,26,36] We used 4 positive (graduation, falling in love, birthday party, travelling) and 4 negative themes (suicide of a friend, divorce of parents, passing away of a grandparent, end of a relationship), about which we wrote a coherent and an incoherent story each. Subsequently, two colleagues specialized in the field independently and blind for condition coded these 16 narratives for coherence using the Narrative Coherence Coding Scheme (NCCS; [24]).…”
Section: Materials and Measuresmentioning
confidence: 99%
“…[24]. The concept has been predominantly investigated in the face of negative life events (trauma) and with regard to the risk of developing symptoms of depression [25][26][27] and PTSD, in multiple populations like terror attack survivors [28] and persons who recently got divorced [29]. In these studies, those who were able to construct a coherent story about their negative life experiences or trauma, appeared to have better mental health than those who were not able to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Also findings that narrating potentially traumatic experiences from a distanced present, rather than from an immersed past perspective is related to well-being (Kross and Ayduk, 2017) indirectly supports the positive role of AR which does require stepping back from the events to embed them in the life story. In their review, Adler et al (2016) concluded that most narrative studies show a helpful role of AR (e.g., longitudinally, Mitchell et al, 2020).…”
Section: Autobiographical Reasoningmentioning
confidence: 99%
“…For example, research has pointed out an important negative association between cognitive load and narrative coherence, indicating that free executive resources might be crucial in order to construct coherent narratives (Boals et al, 2011;Frattaroli, 2006;Klein & Boals, 2001). Furthermore, studies indicate that depression and rumination negatively relate to memory coherence (Buxton, 2016;Mitchell et al, 2020;Vanaken & Hermans, 2020a;Vanderveren et al, 2019), and that rumination can play a mediating role in the association between narrative coherence and psychopathology in younger adolescents (Habermas & Reese, 2015). A recent study of Vanderveren et al (2020) confirms that the relation between memory coherence and depression is at least partially explained by rumination.…”
mentioning
confidence: 94%
“…In recent years, evidence has been increasing that individuals who are more narratively coherent, fare better psychologically and are less likely to suffer from internalising symptoms of psychopathology, like depression and anxiety (Adler et al, 2018;Chen et al, 2012;McLean et al, 2010;Mitchell et al, 2020;Reese et al, 2011Reese et al, , 2017Vanaken & Hermans, 2020a;Vanderveren et al, 2019). In addition, narrative coherence has also been shown to be positively related to having high-quality social relationships and to experiencing less negative social interactions (Burnell et al, 2010;Vanaken & Hermans, 2020a;Waters & Fivush, 2015).…”
mentioning
confidence: 99%